Incidence of cancer among workers in Norwegian hydroelectric power companies. - Tynes, Tore; Reitan, Jon B; Andersen, Aage (Scandinavian Journal of Work, Environment & Health, 1994)
OBJECTIVES--The goal of this study was to examine whether exposure to electric or magnetic fields is related to cancer. METHODS--The study cohort consisted of 5088 men who had worked for at least one year between 1920 and 1991 for any of eight participating companies which produce and distribute hydroelectric power in Norway. The occupational exposure of these workers included extremely low-frequency electromagnetic fields. Incident cancer cases identified from the Cancer Registry of Norway were analyzed on the basis of the standardized incidence ratio with the Norwegian male population as reference. RESULTS--The incidence of cancer was close to unity for the cohort. The standardized incidence ratio for lymphoma was below unity, whereas those for leukemia and brain tumors were similar to those expected. Calculated cumulative exposure to electric or magnetic fields was not associated with the incidence of leukemia or brain tumors, but an excess of malignant melanoma was shown for the highest category of magnetic field exposure. An analysis of combined possible exposure to oils containing polychlorinated biphenyls and exposure to magnetic fields or possible exposure to electric sparks gave standardized incidence ratios of 265 and 280, respectively, for the higher exposure category. CONCLUSIONS--These results do not support the assumption of a possible association between exposure to electromagnetic fields and leukemia and brain tumors. The possible association between exposure to polychlorinated biphenyls or magnetic fields and risk of malignant melanoma should be further evaluated in future studies.